Correction: Exome sequencing reveals IFT172 variants in patients with non-syndromic cholestatic liver disease. - Magdaléna Neřoldová; Elżbieta Ciara; Janka Slatinská; Soňa Fraňková; Petra Lišková; Radana Kotalová; Janka Globinovská; Markéta Šafaříková; Lucie Pfeiferová; Hana Zůnová; Lenka Mrázová; Viktor Stránecký; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0288907.].